2022
DOI: 10.3390/ma15249034
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization of Mechanical Alloying Conditions of Powder for the Preparation of a Fe-10Al-4Cr-4Y2O3 ODS Nanocomposite

Abstract: Mechanical alloying (MA) of powders represents the first processing step in the production of oxide dispersion-strengthened (ODS) alloys. MA is a time and energy-consuming process also in the production of Fe-10Al-4Cr-4Y2O3 creep and oxidation-resistant ODS nanocomposite, denoted as the FeAlOY, and it deserves to be optimized. MA is performed at two different temperatures at different times. The powder after MA, as well as the microstructure and high-temperature strength of the final FeAlOY, are characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Recent explanations state that severe fragmentation of Y 2 O 3 particles drives them into amorphous sub-particles, making them undetectable to XRD [ 41 , 42 ]. Other authors also found that homogenization of Y 2 O 3 in ODS steel during MA was achieved quickly, whereas for metallic components it took much more time [ 43 ]. Figure 16 shows the XRD pattern of the low intensity Zr and Y 2 O 3 reflections obtained after initial mixing of powders (1 min of MA).…”
Section: Resultsmentioning
confidence: 99%
“…Recent explanations state that severe fragmentation of Y 2 O 3 particles drives them into amorphous sub-particles, making them undetectable to XRD [ 41 , 42 ]. Other authors also found that homogenization of Y 2 O 3 in ODS steel during MA was achieved quickly, whereas for metallic components it took much more time [ 43 ]. Figure 16 shows the XRD pattern of the low intensity Zr and Y 2 O 3 reflections obtained after initial mixing of powders (1 min of MA).…”
Section: Resultsmentioning
confidence: 99%